2013
DOI: 10.1182/blood-2012-05-430413
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapeutic strategies to prevent and treat human herpesvirus 6 reactivation after allogeneic stem cell transplantation

Abstract: Key Points• We have characterized, for the first time, the cellular immune response to HHV6 and defined a hierarchy of immunodominance.• We have developed a GMPcompliant approach to generate polyfunctional T-cell lines that effectively kill HHV6-infected cells and are suitable for clinical use.Human herpesvirus (HHV) 6 causes substantial morbidity and mortality in the immunocompromised host and has no approved therapy. Adoptive transfer of virus specific T cells has proven safe and apparently effective as prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
79
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 51 publications
13
79
0
Order By: Relevance
“…Recent studies have suggested that some peptides from HHV-6 will allow HHV-6-specific CD4 ϩ or CD8 ϩ T cells to recognize HHV-6-infected target cells, thus overcoming the immunosuppressive properties of the virus (51,52). Another challenging issue is the identification of pathogen-derived antigens which can specifically induce and activate virus-specific Treg cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that some peptides from HHV-6 will allow HHV-6-specific CD4 ϩ or CD8 ϩ T cells to recognize HHV-6-infected target cells, thus overcoming the immunosuppressive properties of the virus (51,52). Another challenging issue is the identification of pathogen-derived antigens which can specifically induce and activate virus-specific Treg cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer immunotherapy protocols have demonstrated some effectiveness against virally induced disorders (27), such as in EBVinduced posttransplant lymphoproliferative disorders (28,29), but the treatment of solid tumors such as breast cancer remains a major challenge. Immunodominant epitopes derived from the HHV-6B U54 protein have been described recently (30,31). Coupled to our observation that U54 can inhibit cancer cell growth, expression of U54 in breast cancer cells could give a double advantage: first, by limiting cancer cell proliferation, and second, by "marking" the cells for anti-U54 CD8 T cell recognition and destruction.…”
mentioning
confidence: 95%
“…Cellular immunity is believed to play the major role in this control, as reflected by the deleterious effects of T cell immune response suppression. Recent publications reported the proliferation of CD4 ϩ and CD8 ϩ T cells in response to HHV-6A and HHV-6B antigens in most healthy adults (100)(101)(102). Those studies permitted the fine characterization of a significant number of HHV-6 T cell epitopes but showed the following two important limitations for future investigations: the low frequency of circulating HHV-6-specific T cells, requiring in vitro expansion prior to any functional characterization; and the high degree of cross-reactivity between HHV-6A and HHV-6B epitopes.…”
Section: Interactions With the Immune Systemmentioning
confidence: 99%